Data Analytics in Information Security: Enabling Intelligent Cyber Defense - Darla, Mani Sai Kamal (International Journal of Computing and Engineering, 2025)
The digital metamorphosis period has unnaturally altered cybersecurity paradigms, challenging a shift from reactive defense mechanisms to visionary, intelligence-driven security fabrics. Contemporary trouble geographies encompass expanded attack shells through Internet of effects proliferation, pall relinquishment, and distributed pool models that challenge traditional border-grounded security infrastructures. Data analytics technologies, including Extended Discovery and Response systems, machine learning algorithms, Edge artificial intelligence, and Zero Trust Architecture executions, demonstrate substantial functional effectiveness in trouble discovery, response time reduction, and scalability across distributed computing environments. Healthcare and fiscal sectors show transformative advancements through behavioral analytics and anomaly discovery systems, while cost-benefit evaluations reveal compelling, profitable advantages for visionary security investments over reactive incident response models. Still, advanced cybersecurity executions raise significant ethical concerns regarding surveillance overreach, algorithmic bias in automated decision-making systems, and nonsupervisory compliance challenges across multiple authorities. Balancing security effectiveness with sequestration preservation requires sophisticated, specialized results incorporating sequestration-enhancing technologies while maintaining acceptable trouble discovery capabilities. The elaboration toward intelligent cyber defense systems represents an abecedarian metamorphosis in organizational security postures, demanding careful consideration of technological capabilities, functional conditions, and ethical scores in increasingly connected digital surroundings.